2021
DOI: 10.1109/jphot.2021.3100136
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Quality Factor Photonic Nanojets Generated by Truncated Microtoroid Structures

Abstract: A photonic nanojet (PNJ) is a highly confined light beam that focuses from the shadow side of microparticles. In 46.47 this work, we propose a PNJ with ultrahigh quality factor formed by dielectric truncated microtoroid. The key properties of PNJ, such as the maximum intensity, the length of PNJ, the full-width at half maximum (FWHM), are studied in detail using finite-difference time-domain (FDTD) analysis. The results show that a PNJ with an enhanced intensity of 55.21 times to the incident light, superlong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Simulations have shown that the greatest beam curvature can be obtained when the remote segment is irradiated near the Brewster angle 30 . Combining key parameters of the photonic hook, and having in mind the quality criteria for the photonic jet 31 , we propose to characterize the PH by a quality criterion Q as…”
Section: Double Photonic Hookmentioning
confidence: 99%
“…Simulations have shown that the greatest beam curvature can be obtained when the remote segment is irradiated near the Brewster angle 30 . Combining key parameters of the photonic hook, and having in mind the quality criteria for the photonic jet 31 , we propose to characterize the PH by a quality criterion Q as…”
Section: Double Photonic Hookmentioning
confidence: 99%
“…Gu et al used liquid-filled microspheres to generate an ultralong PNJ in 2015 [30], Victor Pacheco-Pena et al reported a method of generating PNJs based on the periodic arrangement of a 3D dielectric cuboid micro-structure in 2016 [31], and Geints et al presented a systematic study of the key characteristics (field intensity enhancements, spatial extents) of 2D and 3D photonic nanojets (PNJs) produced by geometrically regular micron-sized dielectric particles illuminated by a plane laser wave in 2018 [32]. Recently, we obtained an ultrahigh-quality factor PNJ Materials 2023, 16, 3146 2 of 12 from truncated microtoroid structures [33], and Xing et al investigated a curved truncated dielectric microcylinder structure using the finite element method, which can form an ultralong PNJ with the longest effective length, in 2022 [34].…”
Section: Introductionmentioning
confidence: 99%